MTB android client and reservation communication system - Musvazvi, Nigel Tafadzwa (Midlands State University, 2018)
The emergence of android mobile applications has allowed small and large organizations to market their services effectively and efficiently in both domestic and international markets. The problem that led to the development of the system was poor communication between the organization and clients and also there was excessive use of paper work. Furthermore some clients were not committed to their reservations there have been made as result of this the organization was left without concrete evidence to charge them. The purpose of this study was therefore to come with an android, client and reservation communication system. The objective of the study was to facilitate communication between clients and the organization. The researcher further investigated how the current system works and in-depth understanding of the problem area was gained through the use of the following research techniques, interviews, observations and questionnaires. The system comprised of web application and android application. The web application serves the organization and it acts as back end application which was developed using Php laravel. The android application is for the clients and it was developed using the android studio. In implementing the system the author used the parallel change over strategy whereby the proposed system will be running concurrently with the existing. Training was also done so that the users will know how to operate the new system developed. Conclusively the system was greatly appreciated by both the clients and the organization. The researcher recommended organization to add at least workers to work with the system. Furthermore the author recommended the firm to change the way the clients view their reservations and also to add a module for message notification.